Australian Aboriginal and Torres Strait Islander Collections of Genetic Heritage: The Legal, Ethical and Practical Considerations of a Dynamic Consent Approach to Decision Making. Issue 1 (2020) - Prictor, Megan; Huebner, Sharon; Teare, Harriet J.A.; Burchill, Luke; Kaye, Jane
Abstract : Dynamic Consent (DC) is both a model and a specific web-based tool that enables clear, granular communication and recording of participant consent choices over time. The DC model enables individuals to know and to decide how personal research information is being used and provides a way in which to exercise legal rights provided in privacy and data protection law. The DC tool is flexible and responsive, enabling legal and ethical requirements in research data sharing to be met and for online health information to be maintained. DC has been used in rare diseases and genomics, to enable people to control and express their preferences regarding their own data. However, DC has never been explored in relationship to historical collections of bioscientific and genetic heritage or to contexts involving Aboriginal and Torres Strait Islander people (First Peoples of Australia). In response to the growing interest by First Peoples throughout Australia in genetic and genomic research, and the increasing number of invitations from researchers to participate in community health and wellbeing projects, this article examines the legal and ethical attributes and challenges of DC in these contexts. It also explores opportunities for including First Peoples' cultural perspectives, governance, and leadership as a method for defining (or redefining) DC on cultural terms that engage best practice research and data analysis as well as respect for meaningful and longitudinal individual and family participation.